Varicella-Zoster Virus Infection of Primary Human Spinal Astrocytes Produces Intracellular Amylin, Amyloid-β, and an Amyloidogenic Extracellular Environment. (29th October 2019) - Bubak, Andrew N; Como, Christina N; Coughlan, Christina M; Johnson, Noah R; Hassell, James E; Mescher, Teresa; Niemeyer, Christy S; Mahalingam, Ravi; Cohrs, Randall J; Boyd, Timothy D; Potter, Huntington; Russ, Holger A; et al.
Abstract: Background: Herpes zoster is linked to amyloid-associated diseases, including dementia, macular degeneration, and diabetes mellitus, in epidemiological studies. Thus, we examined whether varicella-zoster virus (VZV)-infected cells produce amyloid. Methods: Production of intracellular amyloidogenic proteins (amylin, amyloid precursor protein [APP], and amyloid-β [Aβ]) and amyloid, as well as extracellular amylin, Aβ, and amyloid, was compared between mock- and VZV-infected quiescent primary human spinal astrocytes (qHA-sps). The ability of supernatant from infected cells to induce amylin or Aβ42 aggregation was quantitated. Finally, the amyloidogenic activity of viral peptides was examined. Results: VZV-infected qHA-sps, but not mock-infected qHA-sps, contained intracellular amylin, APP, and/or Aβ, and amyloid. No differences in extracellular amylin, Aβ40, or Aβ42 were detected, yet only supernatant from VZV-infected cells induced amylin aggregation and, to a lesser extent, Aβ42 aggregation into amyloid fibrils. VZV glycoprotein B (gB) peptides assembled into fibrils and catalyzed amylin and Aβ42 aggregation. Conclusions: VZV-infected qHA-sps produced intracellular amyloid and their extracellular environment promoted aggregation of cellular peptides into amyloid fibrils that may be due, in part, to VZV gB peptides. These findings suggest that together with host and other environmental factors, VZV infection may increase the toxic amyloid burden and contribute to amyloid-associated disease progression. Abstract : Varicella-zoster virus infection of astrocytes produces intracellular amylin, amyloid-β, amyloid, and an extracellular amyloidogenic environment due, in part, to amyloidogenic viral peptides. These findings indicate that infection may contribute to the toxic amyloid burden, accelerating amyloid-associated disease progression.